Ayurvedic Interventions in Motor Neuron Disease (International Journal of Ayurveda and Pharma Research, 2024)
Motor neurons are the neurons through which the brain exerts control over skeletal muscles of the body. Motor neuron diseases are rare heterogeneous group of neurologic disorders characterized by progressive degeneration of motor neurons.A 55-year-old woman diagnosed as motor neuron disease was admitted to Vaidyaratnam Ayurveda College Hospital, on 2/11/2023, for a 21 day duration, presenting with complaints of weakness of both upper limbs associated with muscle wasting predominantly on right shoulder and wrist since 1 year. The clinical and laboratory features suggested a diagnosis of brachial amyotophy diplegia, a regional variant of ALS.According to Ayurveda, Avarana vatavyadhis are found to have close resemblance to Motor Neuron Diseases and her symptomology can be correlated to Kaphavruta Vyanavata. The patient underwent Avaranagna and Vata vyadhi chikitsa. Assessment of the patient was done before and after treatment by physical examination, ALSFRS-R and Neuro QoL scale. A satisfactory improvement was observed with gradual gaining of upper limb strength and quality of life. This case study demonstrates that brachial amyotophy diplegia can be symptomatically managed with Ayurvedic therapy.